Toward a More Business Friendly Tax Regime : Key Challenges in South Asia - Reva, Anna (World Bank, Washington, DC, 2015)
This paper discusses competitiveness-related issues surrounding the design and administration of corporate and value added/sales taxes in four South Asian countries -- Bangladesh, India, Pakistan, and Sri Lanka. The paper is based largely on analysis of tax legislation; in addition, data from the World Banks enterprise surveys, the Doing Business report, as well as industry studies are used for evidence on tax compliance costs for business. The review of tax regulations in the region shows several commonalities: (1) widespread use of tax incentives to support selected industries, types of firms, and industrial locations; (2) many exemptions from value-added taxes as well as the practice of levying multiple indirect taxes on the same base; and (3) high costs of tax compliance for businesses. The paper discusses the consequences of tax policies for the competitiveness of South Asian producers, describes the main problems in tax administration, and outlines key directions for reforms.